ANALYSIS OF THE SPECIFICS AND EFFICIENCY IMPROVING FACTORS OF PROJECT MANAGEMENT IN RUSSIA - Novikova, Natalia; Pirozhenko, Natalya; Bokareva, Elena; Dmitrieva, Nina (Revista Inclusiones, 2019)
The transition of the Russian economy to dynamic post-crisis development requires the high activity of economic entities. Improving the efficiency of organizations’ project management, especially innovative, should lead to accelerated modernization of the national economy, which is one of the most important conditions for successful economic restructuring. This should help to create conditions for ensuring rapid economic growth, long-term sustainable development of the Russian economy, as well as improving the welfare of Russian society.